Mitochondrial genome of Salix cardiophylla and its implications for infrageneric division of the genus of Salix. Issue 3 (2nd July 2020) - Chen, Xiong; Zhang, Li; Huang, Yuan; Zhao, Fuwei
Abstract: Salix cardiophylla was a member of the genus of Salix in family Salicaceae with unique morphological traits, and once recognized as a separate genus, Toisusu Kimura. Here, we sequenced and assembled the complete mitochondrial genome of S. cardiophylla, which was 735, 173 bp in length, including 56 genes, 28 protein-coding genes, 3 rRNA genes, 25 tRNA genes, and one large inverted repeat regions with length of 13, 603 bp. Phylogenetic analysis based on 26 mitochondrial CDS confirmed that S. cardiophylla is a member of Salix, and support its merge into Salix in aspect of our new insights on mitogenome phylogenomics.